Кафедрі геодезії - 140 років - Ярема, Н. П. (Видавництво Львівської політехніки, 2011)
Рассмотрена история создания кафедры геодезии Национального университета “Львивська политехника”. Описаны основные этапы развития кафедры. The history of the geodesy department of National university “Lviv polytechnic” is considered. All basic stages its development is described.